PRINCIPLES OF DRAMATURGY OF DANCE AND THEIR USAGE IN THE PROCESS OF STUDYING COMPOSITION - Spalva, Rita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
Contemporary scholars are increasingly turning to dramaturgy of dance since it is a fairly recent phenomenon in develpopment of dance in the age of poststructuralism. In light of this there are masterclasses forums and other forms of group work abounding. These lead the way in the debate concerning the role of director in the artistic process as well as regarding the new forms of cooperation in the context of contemporary choreography. With that in mind, analysis in the history of dance, suggests that questions concerning dramaturgy of dance has been a core issue for choreographers since early days of ballet. Significance of the article lies in the analysis of the classic laws of dramaturgy of dance and their usage in the process of studying the composition of dance. The subject is seen through the work of Andre Lepecki, Rotislav Zaharov, Igor Smirnov, Jacqueline Smith –Autard and other. The goal of the article is to analyze principles of the dramaturgy of dance in the context of Russian school of dance and to investigate their efficiency ir the process of studying composition. The subject of research are the principles of dramaturgy of dance. The methods used in the research – analysis of scientific literature, theory of dance and pedagogical experience.